Effects of Intratympanic Injection of Isosorbide on the Vestibular Function of Animal Models of Endolymphatic Hydrops - Minbum Kim (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2021)
Objectives The aims of this study were to investigate the effects of intratympanic injections of isosorbide on vestibular function in animal models of endolymphatic hydrops and to find a new treatment option for the acute onset of vertigo in Ménière disease (MD). Methods Seventy male guinea pigs received intratympanic injection of isosorbide (IT-ISB). The animals were divided into three study groups: control, a chronic hydrops model, and an acute hydrops model. Intracochlear drug concentrations were measured using high-performance liquid chromatography. Vestibular function was analyzed using an animal rotator test with bidirectional sinusoidal harmonic acceleration before and after IT-ISB administration. Histological changes were also investigated. Results ISB successfully permeated the perilymph through the round window membrane (RWM) at all three concentrations (25%, 50%, and 100%). In the chronic hydrops model, while IT-ISB histologically induced a reduction of endolymphatic hydrops, vestibular function was unchanged. In the acute hydrops model, no endolymphatic hydrops was histologically observed, and vestibular symmetry was also preserved after IT-ISB. Conclusion ISB passed through the RWM into the perilymphatic space even at lower concentrations. IT-ISB histologically reduced hydrops in the chronic model and preserved symmetrical vestibular function in the acute model. IT-ISB could be a treatment candidate for acute attacks of vertigo in MD.